Peningkatan Kapasitas Pemerintah Negeri dan Saniri Dalam Pembentukan Peraturan Negeri Di Negeri Hila, Kecamatan Leihitu, Kabupten Maluku Tengah - Pattinasarany, Yohanes; Salmon, Hendrik; Singkery, Michael Rolando (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: State Regulations are written regulations stipulated by the head of the state government after being discussed and agreed upon with the state officials as the legal basis for implementing government at the state level, including in Hila State. To form a good state regulation that can apply effectively in society, a system of formation is needed that can support its formation from the preparation and program development stage, the design stage, discussion to promulgation, to the enforcement or implementation stage in society. In reality, this condition has not been able to be realized well in the countries in Central Maluku district, including in Hila Country, Leihitu District, Central Maluku Regency, so in this trial the following problems were identified: (1) To what extent is the understanding of the State Government and Saniri of Hila Country in forming State Regulations. (2) Factors that influence the State and Saniri governments of Hila State in forming State regulations?.Purposes of Devotion: The aim of this service is to transfer knowledge through training in drafting State Regulations to the State Government, Saniri State and the people of Hila State.. Method of Devotion: The service method is empirical, with the initial approach carried out through coordination with the State Government and Saniri Negeri for the service team to carry out the process of introducing the activities to be carried out and their correlation with government administrators in the State.Results of the Devotion: The results of the trial show that the State Government and Saniri of Hila State do not yet understand the exercise of authority in forming State Regulations as the legal basis governing the exercise of state authority, both authority based on rights of origin and local scale authority of the country, as well as government affairs assigned by the government or regional government. There are three important factors that are the main reasons why the state government and saniri of Hila state have not been able to form their own state regulations. The factors referred to are First, the Human Resources factor, the absence of assistance by the regional government, or government agencies, including universities, is a factor in determining the program.